EXTH-21. DIFFERENTIAL PROTEIN EXPRESSION LEVELS OF ABC AND SOLUTE CARRIER TRANSPORTERS AT THE BLOOD-BRAIN BARRIER OF HUMAN BRAIN AND GLIOBLASTOMA. (11th November 2019) - Bao, Xun; Wu, Jianmei; Xie, Youming; Kim, Seongho; Michelhaugh, Sharon; Jiang, Jun; Mittal, Sandeep; Sanai, Nader; Li, Jing
Abstract: BACKGROUND: Mechanistic understanding and quantitative prediction of drug penetration across the human blood-brain barrier (BBB) is critical to rational drug development and treatment for brain cancer especially glioblastoma. However, prediction of drug brain/tumor penetration has been significantly hindered mainly due to the lack of quantitation data on transporter protein expression levels at the human BBB. This study was to determine protein expression levels of major transporters and markers at the BBB of human brain and glioblastoma. METHOD: The absolute protein expression levels of major transporters and markers were determined in isolated microvessels of human brain (N=30), glioblastoma (N=47), rat (N=10) and mouse brain (N=10), using liquid chromatography with tandem mass spectrometry (LC-MS/MS) based targeted proteomics. RESULTS: In isolated microvessels of 30 human brain specimens, the median protein abundances for ABCB1, ABCG2, GLUT1, GLUT3, LAT1, MCT1, Na/K ATPase, and Claudin-5 were 3.38, 6.21, 54.51, 7.17, 3.42, 5.71, 32.14, and 1.15 fmol/µg protein, respectively. In glioblastoma microvessels, ABCB1, ABCG2, MCT1, GLUT1, Na/K ATPase, and Claudin-5 protein levels were significantly reduced, while LAT1 was increased and GLU1 remained the same. ABCC4, OATP1A2, OATP2B1, and OAT3 were undetectable in isolated microvessels of both human brain and glioblastoma. There was species difference in transporter protein expression levels in isolated microvessels of human, rat and mouse brain. Specifically, rodent BBB expressed significantly higher ABCB1 but similar ABCG2, as compared to human BBB. CONCLUSION: The physical and biochemical barriers of the BBB in glioblastomas are largely disrupted, as indicated by the loss or significant reduction in protein expression of the tight junction marker (claudin-5), brain endothelial cell marker (GLUT1), and major efflux transporters (ABCB1 and ABCG2) as compared to normal human BBB. Differential BBB transporter protein expression levels provides mechanistic and quantitative basis for the prediction of heterogeneous drug penetration into human normal brain and glioblastoma.